Metaphor As Knowledge. A Hermeneutical Framework for Biblical Exegesis with a Sample Reading from the Song of Songs (Song 8:10) - Verde, Danilo (The Biblical Annals, 2016)
The main purpose of this article is to provide biblical scholarship with a broad hermeneutical framework concerning the cognitive dimension of metaphorical phenomena. According to current research, metaphor is a tool of knowledge, a way through which the human mind conceptualizes reality. Despite the fact that Cognitive Linguistics (CL) is generally credited with bringing the cognitive dimension of metaphor to light, the discovery of this dimension is by no means recent. This article will show that it already appeared in Aristotle’s work, was blurred in Classical Rhetoric by a more aesthetic perspective, reappeared at the very beginning of the modern age, and finally became dominant in the 20th century. CL is therefore the result of a long tradition that has the merit of clarifying the cognitive mechanisms of metaphorical processes. Its theoretical and methodological model currently represents the reference point for studies on daily and literary metaphors, shedding new light on biblical metaphors. This article shows how CL can be beneficial for biblical exegesis by analysing Song 8:10 in light of this approach.